Muricidae Gastropod Operculum Extract as a Unique Agent against the Osteosarcoma Cell Line: Unveiling its Anti-Angiogenic and Antioxidant Potential - Chelladurai, Gurusamy; Iyappan, Petchi; Muruganandham, Chandramohan; Ponnaiah, Paulraj (Asian Journal of Biological and Life Sciences, 2025)
Aim: India exports the marine Gastropod operculum, which is used in herbal medicine in Indian communities. Background: Because of its usage in traditional medicine, the operculum provides a source of bioactive chemicals. Free radical scavenging activity, reducing power movement, and H2O2 radical scavenging activity all contributed to the antioxidant potential. The anticancer compounds in clinical characteristics are particularly well represented by natural chemicals extracted from molluscs and their structural counterparts. Materials and Methods: The gastropod protein extract provides several benefits as a prospective material for anticancer treatments with no adverse effects. The pharmacodynamic effects of a chloroform extract from Chicoreus ramosus were explored in cell lines through the Mossman technique for cytotoxicity assay. Results: The cell viability of MG-63 cells ranged from 31.33% to 99.73% at a dosage of 500 μg/mL. The anti-inflammatory properties and processes of action may be linked to flavonoids, which are known to prevent membrane lysis, albumin denaturation, and protease activity. The maximal dose of 100 g/mL inhibited branching points and reduced first-order blood vessels. Both treatment and control CAM had abnormal artery branching and shape. Conclusion: According to the findings, Chicoreus ramosus contains antioxidant, anti-inflammatory, and anti-tumour angiogenic and proliferative properties and might be a source for the creation of novel anti-cancer drugs.
Keywords: Angiogenic activity; Anti-inflamatory; Anticancer; Antioxidant; Chicoreus ramosus